Medical technology in India: Tracing policy approaches - Indira Chakravarthi (Wolters Kluwer Medknow Publications, 2013)
Medical devices and equipment have become an indispensable part of modern medical practice. Yet these medical technologies receive scant attention in the Indian context, both at the health policy level and as an area of study. There has been little attempt to systematically address the issue of equipment based medical technologies and how to regulate their use. There is paucity of primary data on the kind of medical equipment and techniques being introduced, on their need and relative usefulness, reliability, patterns of utilization, on their production, procurement, distribution, costs, and accessibility. This article reviews some of the policy issues relating to equipment based medical technology in India, in light of the specific choices and policies made during and after the colonial period in favour of modern medicine and a technology-based public health system, attempts at self-sufficiency and the current international environment with respect to the medical equipment and health-care industry.